Normalizing effect of composite “Lymphosilica” on biochemical parameters of blood and manifestation of metabolic syndrome - Ostrovska, G.V.; Pazyuk, L.M.; Krupska, T.V.; Roslova, N.М.; Tkachenko, О.V.; Turov, V.V.; Dzerzhynsky, M.E. (Reports of the National Academy of Sciences of Ukraine, 2019)
It has been shown that a high-calorie diet in rats for 100 days leads to the development of certain manifestations of obesity and metabolic syndrome, which are expressed in an increase in the body weight and visceral fat, the development of primary and secondary stages of parenchymal fatty degeneration with a decrease in the morphological manifestations of synthetic activity of the nucleus, with slight variations on the biochemical level. The introduction of phytopreparations with a high content of polyphenols, as well as flavonoids, terpenes of polysaccharides, leads in some cases to manifestations of “adaptive strain” of liver hepatocytes, both in the standard diet and in the background of a high calorie ration. The positive influence of the composite system on the basis of highly dispersed silica and phyto-raw materials with high content of polyphenols on a reduction of the proportion of visceral fat in the body of rats at the standard diet, the normalization of the level of bilirubin and its fractions, as well as a decrease in the level of cholesterol and alkaline phosphatase in the background of modeling obesity, increasing globulin fractions of blood serum, and protective action in relation to dystrophic changes in liver tissue in the background of alimentary obesity.